Kontribusi Testimoni dalam Meningkatkan Efektivitas Pendidikan Kesehatan tentang Napza di Kabupaten Sleman - Ririn Puspandari, IM Sunarsih, Rendra Widyatama (Fakultas Kedokteran Universitas Gadjah Mada, 2008)
Background: Drugs abuse including narcotic, alcohol, psychotropic and other addictive elements (Napza) keep increased. Teenager is a high risky group toward external bad influence including Napza. The increasing tendency of the number of drugs abuse and the age of drug user which tend to be younger, demanded prevention effort and appropriate control. School as education institution is an appropriate place to prevent drugs abuse by giving right information through health education. The appropriate method that needs to be selected should be suitable with situation and condition in the school in order to create an optimum result.Objective: Health education for drugs abuse through speech with audiovisual, speech by presenting former of user (testimony) and group discussion was expected could influenced on the level of knowledge and changed student’s attitude toward drugs abuse prevention. This research was aimed to find out the influence of health education through speech with audiovisual as well as through speech with testimony and group discussion toward knowledge and attitude of students in the prevention of drugs abuse.Method: This was a quasi experimental research that used Solomon four group designs. The research subject was consisted of two treatment groups and two control groups. The data was collected with questioner regarding knowledge and attitude. Data processing and analysis was used student t-test and anova.Result: There was a knowledge improvement on the first treatment group that used interactive speech and audiovisual as well as in the second treatment group that used interactive speech method, testimony and group discussion (p<0,05). There was a significant improvement on attitude toward drugs abuse prevention in the group with interactive speech, testimony, and group discussion. There was a difference on knowledge between both of the methods toward improvement on attitude and yet there was a difference on knowledge toward knowledge improvement.Keywords: health education, testimony, knowledge, attitude and drugs abuse